2021
DOI: 10.1002/anie.202010616
|View full text |Cite
|
Sign up to set email alerts
|

Boron in Prebiological Evolution

Abstract: Boron(III), as borate (or boric acid), mediates the synthesis of ribose, ribonucleosides, and ribonucleotides. These reactions are carried out under moderate temperatures (typically 70–95 °C) with organic molecules (or their derivatives) detected in interstellar space and inorganic ions found in minerals on Earth (and could occur during early stages of prebiotic evolution). Research in this century suggests that borate was a relevant prebiological reagent, thus reinforcing the RNA world hypothesis as an explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…Hematite has also been used in the prebiotic synthesis of GP [6]. Similarly, borates (including ulexite) have been considered to have played an important role in the chemical origin of biological molecules, particularly in the plausible stability of sugars [20][21][22], even though their presence on the Hadean Earth is somewhat questionable [23]. Olivines ([Fe,Mg] 2 SiO 4 ) are considered to be one of the most ubiquitous and primitive minerals on the Earth [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Hematite has also been used in the prebiotic synthesis of GP [6]. Similarly, borates (including ulexite) have been considered to have played an important role in the chemical origin of biological molecules, particularly in the plausible stability of sugars [20][21][22], even though their presence on the Hadean Earth is somewhat questionable [23]. Olivines ([Fe,Mg] 2 SiO 4 ) are considered to be one of the most ubiquitous and primitive minerals on the Earth [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The AI-2 quorum-sensing autoinducer and subsequent transformation in a borate-diester furanosyl structure generate the active form complex [ 164 ], which implies that B is involved in signalling pathways; furthermore, the demonstration that borate is required for the synthesis of stable pentoses, including ribose [ 5 ], suggested that B was involved in the prebiotic synthesis of biomolecules. Later, it was described that the in vitro synthesis of ribonucleotides was enhanced by B binding to 2′ and 3′ positions [ 167 ]. Therefore, it was considered that B could be a “staple” element that stabilizes the synthesis and/or activate molecules.…”
Section: Boron Complexing Moleculesmentioning
confidence: 99%
“…However, to date, there is no experimental evidence of in vivo borate-complexing with nucleotides. Moreover, B was hypothetically important for the stable prebiotic synthesis of ribonucleotides [ 167 ], but once synthesized, the phosphate at the 5′-position destabilizes borate bound to ribose [ 206 ]. This can explain why SAM has a higher affinity for B binding and, at the same time, does not support the in vivo complexation of ribonucleotide phosphates.…”
Section: Boron Complexing Moleculesmentioning
confidence: 99%
“…[62] Franco and da Silva pointed to the possible importance of boron-containing minerals in the prebiotic synthesis of ribonucleotides. [65] Furthermore, it has been suggested that microcavities in rocks [66,67] can serve as reaction compartments [55,68,69] (Figures 1 and 2c). Hansma formulated the mica hypothesis, which entails that the gaps between mica sheets can act as cell-like compartments.…”
Section: Minerals and Rocksmentioning
confidence: 99%
“…[ 62 ] Franco and da Silva pointed to the possible importance of boron‐containing minerals in the prebiotic synthesis of ribonucleotides. [ 65 ]…”
Section: Relevant Prebiotic Conditionsmentioning
confidence: 99%